Impact of Chronic Smoking on Choroidal Thickness: A Comparative Analysis Using Optical Coherence Tomography - Ranabir Mazumdar; Subhamitra Maulik; Nazir Abdul Wasim (International Journal of Integrated Health Sciences)
Background: Chronic smoking has systemic vascular effects, including alterations in ocular blood flow and choroidal thickness, impacting visual health.